The Relationship between Parental Parenting and the Incidence of Child Stunting in Poor Families in the Working Area of the Limboto Health Center - Adisty Anggrayuni Yunus; Zuriati Muhamad; Dewi Modjo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Stunting is a condition in which a person is shorter than usual based on his or her age and gender. The impact of long-term stunting is non-optimal posture in adulthood (shorter than in general), increased risk of obesity and other diseases, decreased reproductive health, suboptimal learning and performance capacity, productivity and suboptimal work capacity. Parenting is one of the factors that is closely related to child growth and development. Objective: This study aims to determine the relationship between parental parenting and the incidence of child stunting in poor families. Methods: This study is a quantitative research with an analytical survey approach and using a cross-sectional research design, the number of population, namely the total number of children under five at the Limboto Health Center from December 2024 to January in 2025 as many as 1,296 children under five and the number of samples used is 93 children under five using the Slovin formula. Results: The highest parental parenting style in poor families is democratic parenting as many as 43 people while the highest incidence of child stunting is 54 people with a significant value or Pvalue of 0.000 or <0.05. Conclusion: there is a relationship between parental parenting and the incidence of child stunting in poor families in the working area of the Limboto Health Center in the working area of the Limboto Health Center. Suggestion: For Puskesmas to provide parents with an understanding that parents have an important role in preventing or handling stunting and reviewing in terms of providing PMT so that it is right on target. For parents to provide good parenting to children such as paying attention to children's diet, children's personal hygiene, children's lifestyle patterns and paying attention to the environment where children live.